Mapping of Notch signaling in the developing organ of Corti in common marmosets - Hosoya, Makoto; Fujioka, Masato; Okano, Hideyuki; Ozawa, Hiroyuki (Frontiers in Neuroanatomy, 2023)
Introduction The well-regulated development of the sensory epithelium is essential for hearing. This process involves the specification of a pro-sensory epithelium containing common progenitors that differentiate into hair and supporting cells. Notch signaling is one of the most critical pathways during these processes, and its modification is thought to be a feasible approach for treating hearing loss. Despite interspecies differences between rodents and primates or humans, most of our current knowledge regarding cochlear development has been obtained from rodent models. Methods We therefore examined and mapped the expression patterns of Notch signal components in the developing cochlea of the common marmoset (Callithrix jacchus), a small monkey species native to the New World, a primate model animal. Results In contrast to the preserved expression patterns of the Notch signaling components in the hair cell differentiation between primates and rodents, we unveiled relatively large interspecies differences during the maturation of supporting cells. Discussion This improved knowledge of Notch signaling during primate cochlear development will facilitate the development of future regenerative therapies.